Pengaruh Pembelajaran Problem Based Learning Dalam Meningkatkan Kreativitas Dan Kemampuan Berfikir Kritis Mahasiswa: (The Effect of Problem-Based Learning in Increasing Students' Creativity and Critical Thinking Ability) - Hidayati, Fajrina; Solida, Adila; Wisudariani, Evy (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
Creative thinking is a mental activity that a person uses to build new ideas or ideas. To develop student creativity, a good and innovative learning process is needed. One of the learning models that can actively involve students and increase student creativity is Problem Based Learning (PBL). The purpose of this study was to identify differences in students' creativity and thinking skills between the application of case-based learning and conventional learning in the vector control and rodent courses. This research was conducted at the Department of Public Health, University of Jambi in the fifth semester students with an interest in environmental health with a total of 37 students. The research design was in the form of a quasi-experimental class involving the experimental class and the control class. The instrument used is a test sheet with indicators to measure thinking ability and creativity, a communication skill test sheet, and an assessment report sheet. Data were collected twice through pre-test and post-test. Processing and data analysis using Paired Sample T-Test. The results showed that most of the students were still less active during lectures using the conventional / lecture method, as many as 15 people (40.5%). Students only pay attention, remain silent and there are no questions or comments related to the lecture material presented. The results of the statistical test showed that the p.value was 0.000, the p-value < Î± (0.05), which means that there is a difference in student learning outcomes using the conventional / lecture method using the PBL method. This means that there is an effect of giving the PBL learning method on the thinking ability (learning outcomes) of fifth-semester students with an interest in environmental health, majoring in public health sciences, FKIK Jambi University in vector control and rodent courses. This study concludes that the application of the case-based learning model is expected to increase students' creativity and thinking skills and hone communication skills by being actively involved in a complex learning process based on case studies. Abstrak. Untuk mengembangkan kreativitas siswa, diperlukan proses pembelajaran yang baik dan inovatif. Salah satu model pembelajaran yang dapat melibatkan siswa secara aktif dan meningkatkan kreativitas siswa adalah Problem Based Learning (PBL). Tujuan penelitian ini adalah untuk mengidentifikasi perbedaan kreativitas dan kemampuan berpikir kritis mahasiswa dengan metode PBL pada mata kuliah pengendalian vektor dan hewan pengerat. Penelitian ini dilakukan di Jurusan Kesehatan Masyarakat Universitas Jambi pada mahasiswa semester V peminatan kesehatan lingkungan dengan jumlah 37 mahasiswa. Desain penelitian ini berupa kelas eksperimen semu yang melibatkan kelas eksperimen dan kelas kontrol. Analisis data menggunakan Paired Sample T-Test. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa masih kurang aktif pada saat perkuliahan menggunakan metode konvensional/ceramah yaitu sebanyak 15 orang (40,5%). Hasil uji statistik menunjukkan bahwa p.value adalah 0,000, nilai p < (0,05), yang berarti terdapat perbedaan hasil belajar siswa yang menggunakan metode konvensional/ceramah dengan menggunakan metode PBL. Artinya ada pengaruh pemberian metode pembelajaran PBL terhadap kemampuan berpikir (hasil belajar) mahasiswa semester V minat kesehatan lingkungan jurusan ilmu kesehatan masyarakat FKIK Universitas Jambi pada mata kuliah pengendalian vektor dan hewan pengerat. Diharapkan dapat meningkatkan kreativitas dan keterampilan berpikir siswa serta mengasah keterampilan komunikasi dengan terlibat aktif dalam proses pembelajaran yang kompleks berdasarkan studi kasus.